2021
DOI: 10.15689/ap.2021.2001.17426.07
|View full text |Cite
|
Sign up to set email alerts
|

Evidências Adicionais de Validade da Escala de Satisfação no Trabalho

Abstract: Este estudo objetivou identificar as propriedades da escala de satisfação no trabalho mais utilizada em amostras brasileiras em termos de sua estrutura, invariância da medida e validade convergente. Participaram da pesquisa 733 trabalhadores (46% mulheres) do setor industrial e terciário de dois estados brasileiros. Além do modelo original de cinco fatores correlacionados, foram comparados três modelos estruturais alternativos (cinco fatores não correlacionados, hierárquico e bifatorial). Os resultados apontam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The results showed that although the JSS is not a scale used in many international studies, it is the most widely used in Brazil (Carvalho et al, 2021), which is justified by its strong adaptation to the Brazilian cultural reality (Hora et al, 2018). In this sense, the analysis of the JSS dimensions resulted in adequate levels of reliability, conditions that allowed the instrument to be evaluated as valid, an aspect that converges with Rueda (2015) and Carvalho et al (2021).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results showed that although the JSS is not a scale used in many international studies, it is the most widely used in Brazil (Carvalho et al, 2021), which is justified by its strong adaptation to the Brazilian cultural reality (Hora et al, 2018). In this sense, the analysis of the JSS dimensions resulted in adequate levels of reliability, conditions that allowed the instrument to be evaluated as valid, an aspect that converges with Rueda (2015) and Carvalho et al (2021).…”
Section: Discussionmentioning
confidence: 97%
“…The results showed that although the JSS is not a scale used in many international studies, it is the most widely used in Brazil (Carvalho et al, 2021), which is justified by its strong adaptation to the Brazilian cultural reality (Hora et al, 2018). In this sense, the analysis of the JSS dimensions resulted in adequate levels of reliability, conditions that allowed the instrument to be evaluated as valid, an aspect that converges with Rueda (2015) and Carvalho et al (2021). When referring to teachers' job satisfaction, Cardoso and Costa (2016) highlight that this topic has received little attention from educational institutions, especially due to its influence on organizational success and student learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of emotional intelligence uses self-awareness, self-management, self-motivation, empathy, and relationship management (Boyatzis, 2018;Nguyen et al, 2019). Meanwhile, job satisfaction is measured using salary, promotion, benefits, rewards, and job flexibility (Carvalho et al, 2021;Gazi et al, 2022). Lastly, employee performance measurement uses job quality, job quantity, punctuality, effectiveness, and autonomy (Jang et al, 2023;Samihardjo & Hapsari, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Employees' job satisfaction can be measured using salary, promotion, benefits, rewards, coworkers, superior-subordinate relationships, communication, and job flexibility (Carvalho et al, 2021;Gazi et al, 2022). These indicators are reported to affect employee's perception of workplace conditions.…”
Section: Introductionmentioning
confidence: 99%